Tectonostratigraphy of the Southern Part of Papua and Arafura Sea, Eastern Indonesia - Bhakti H. Harahap (Geological Agency, 2012)
DOI: 10.17014/ijog.v7i3.145Sedimentary history and stratigraphy of the Papua and Arafura Sea areas, eastern Indonesia, are gained from surface geological mapping combined with published data from oil companies. Development of some sedimentary units demonstrates that the tectonism have influenced sedimentation of such units comprising a succession of Phanerozoic rocks developing in a stable continental margin. The succession underlain by Cambrian-Silurian-Devonian metamorphic rocks consists of Tuaba, Kariem, Awitagoh, and Kemum Formation, and Modio Dolomite (Pre-Rift Phase). These rocks having been intruded by Late Permian-Middle Triassic granitoids and Carboniferous granite, are unconformably overlain by Late Carboniferous to Cretaceous siliciclastic-rich units comprising Aifam Group and Tipuma Formation (syn-Rift Phase) and Kembelangan Group (Mesozoic Passive Margin Post-Rift). The Aifam Group is separated by a regionally continuous boundary on its top contact from the Triassic-Early Jurassic Tipuma Formation, which filled the block-faulted rift valley subbasins of continentally deposited red beds in the breakup stage. Regionally, developed erosion surfaces of the breakup unconformity have separated these red beds from generally transgressive post-breakup deposits of the Jurassic to Cretaceous marine sediments of the Kembelangan Group. Beach to shallow marine-glauconitic sandstone and shale of the group pass upward into shelf mudstone. Relative sea level fall related to the tectonic stability of the area led to the development of Eocene to Late Miocene platform carbonates of the New Guinea Limestone Supergroup which occurred in the entire island of Papua and the southern of Arafura that overlie these non-carbonate units (Tertiary passive margin). It is separated from the siliciclastic-rich packages by the Tertiary - Pre-Tertiary boundary. The sea level fluctuation within the group was also recorded during the formation of thin, discontinuous sandstone beds/lenses of Sirga Formation and Adi Member of the Oligocene age (Convergence phase). Turbidite sediments of the Miocene Klasafet Formation was deposited in a deep marine environment at the same time as the eruption of magmatic arc (Compressional phase). The mainland area was exposed above sea level at Late Miocene to Pleistocene (Melanesian Orogeny) and terrigenous detritus deposition began to fill in the basin as molasses type deposits with a marine influence in part (Buru and Steenkool Formations).